Pancreatic pseudocysts: Results of surgical treatment - Delgado, Bolivar; Larre Borges, Uruguay (Cirugía del Uruguay, 1971)
The results obtained in the surgical treatment of pancreatic pseudocyst are revised with special emphasis on ethiology and the procedures applied, and with reference to a serie of 15 cases presented by the authors.